Robotic right hemicolectomy for transverse colon cancer in a patient with stringer type IIa intestinal malrotation: a case report with intraoperative video - Go Ito; Dai Shida; Jun Imaizumi; Junko Mukohyama; Satoko Monma; Naoki Sakuyama (Frontiers in Surgery, 2026)
Background Intestinal malrotation results from disrupted midgut rotation and fixation during embryogenesis. Pure duodenal non-rotation (Stringer Type IIa), featuring isolated duodenal malrotation with a normally positioned colon, is extremely rare. Its unique anatomical distortions—specifically the absence of standard duodenal landmarks—present significant challenges for colorectal surgery. Case description An asymptomatic 61-year-old male was diagnosed with transverse colon cancer during routine screening. Preoperative three-dimensional computed tomography revealed Type IIa malrotation: a vertically descending duodenum lacking the horizontal portion and a reversed distal relationship between the superior mesenteric artery and vein. We performed a robotic-assisted right hemicolectomy. To navigate the altered anatomy safely, we utilized a lateral-to-medial approach, providing an early anatomical roadmap before vascular dissection. The robotic platform's high-definition visualization facilitated precise identification of distorted vasculature and safe D3 lymphadenectomy. Pathological examination confirmed pT3N0M0, Stage IIA. The postoperative course was uneventful except for a minor surgical site infection; the patient remains recurrence-free at 3-year follow-up. Conclusion Pure duodenal non-rotation presents unique challenges, including loss of the duodenal C-loop landmark and mesenteric vascular reversal. Preoperative recognition through detailed imaging is essential for safe surgical planning. This case demonstrates that robotic surgery is safe and efficient in complex settings via a strategic lateral-to-medial approach. The accompanying video provides a valuable resource for managing this rare anomaly.